Marine protected areas overall success evaluation (MOSE): A novel integrated framework for assessing management performance and social-ecological benefits of MPAs. (1st December 2020) - Picone, F.; Buonocore, E.; Claudet, J.; Chemello, R.; Russo, G.F.; Franzese, P.P.
Abstract: Characterized by interlinked social, economic, and ecological dynamics, Marine Protected Areas (MPAs) are a management tool for achieving sustainability goals in social-ecological systems. The recent increase in their establishment worldwide, fostered by international policies, highlights the need for comprehensive and integrated assessment frameworks able to address the evaluation of their social-ecological effectiveness and management performance, which is of fundamental importance for their adaptive management and decision making processes. Although several indicators and methodologies exist to assess MPAs ecological or social performances, no comprehensive assessment framework currently captures their broad range of objectives, encompassing the ecological, socio-cultural, and economic spheres. In this study, we present a novel quantitative framework (named MPAs Overall Success Evaluation – MOSE) able to assess the overall effectiveness and management performance of MPAs under the perspective of social-ecological systems. The multicriteria framework includes indicators linked to nature conservation, socio-cultural, socio-economic, and management objectives, integrating the multidisciplinary knowledge on MPAs in a single but comprehensive approach. The proposed framework was applied to the case study of Cerbère-Banyuls Natural Marine Reserve (France), the first MPA included in the IUCN Green List. Results showed that a high level of management effort is applied to the investigated MPA, generating several social-ecological benefits. This study showed the applicability of the MOSE framework and its potential usefulness as a tool to inform managers and decision-makers in charge for developing adaptive management strategies. Graphical abstract: Image 1 Highlights: The MPAs Overall Success Evaluation (MOSE) framework is presented. The framework is applied to the Cerbère-Banyuls Natural Marine Reserve (France). Results show the MPA management effort and generated social-ecological benefits. The framework represents a useful tool for adaptive management. Future applications will target a wide variety of MPAs at different scales.